Hamas contained : the rise and pacification of Palestinian resistance - Baconi, Tareq (Stanford University Press, 2018)
"Judicious and impartial, this important work adds nuance to the portrait of one of the Middle East's most divisive players" (Publishers Weekly). Hamas is a multifaceted liberation organization that rules Gaza and the lives of the two million Palestinians who live there. Demonized as a terrorist group in media and policy debates, it has been subjected to accusations and assumptions that have helped justify extreme military action in the region. In Hamas Contained, Tareq Baconi offers the first history of the group on its own terms. Drawing on interviews with organization leaders, as well as publications from the group, Baconi maps Hamas's thirty-year transition from fringe resistance to governance. Questioning the conventional understanding of Hamas, he shows how the movement's ideology ultimately threatens the Palestinian struggle and, inadvertently, its own legitimacy. Baconi demonstrates how Hamas's armed struggle has failed in the face of a relentless occupation, and he argues that Israel's approach of managing rather than resolving the conflict has neutralized Hamas's demand for Palestinian sovereignty. This dynamic has perpetuated a deadlock characterized by its brutality-and one that has led to the collective punishment of millions of Palestinian civilians.
Keywords: Ḥarakat al-Muqāwamah al-Islāmīyah -- History.; Ḥarakat al-Muqāwamah al-Islāmīyah; Palestinian Arabs -- Politics and government.; Palestine -- Politics and government -- 1948-; Gaza Strip -- Politics and government.; Arab-Israeli conflict.; Palestine question (1948-); Palestiniens -- Politique et gouvernement.; Conflit israélo-arabe.; POLITICAL SCIENCE -- Political Process -- Elections.; POLITICAL SCIENCE -- Political Process -- General.; Arab-Israeli conflict; Palestinian Arabs -- Politics and government; Politics and government; Gaza Strip; Middle East -- Palestine; Since 1948; Electronic books.; History